Using Computer Tablets to Assess Preference for Videos in Children with Autism - Chebli, Sabine S. (Behav Anal Pract, 2016)
Using computer tablets, we assessed preference for videos in five children with autism spectrum disorder (ASD). Then, we provided access to most preferred and less preferred videos contingent on sitting on one of two chairs within a concurrent schedule design. All participants spent consistently more time sitting on the chair associated with the video selected the most often during the preference assessment, indicating that practitioners may use the tablet-based assessment procedure to identify potential video reinforcers for children with ASD in applied settings.